THE EFFECT OF PRODUCT QUALITY AND PROMOTION ON CONSUMER SATISFACTION OF RABBANI USERS IN RANCAEKEK DISTRICT BANDUNG REGENCY - Laila Juariyah; Bambang Sucipto (PT. Jurnal Center Indonesia Publisher, 2026)
Abstract The rapid growth of the Muslim fashion industry in Indonesia has intensified competition among Muslim fashion brands, particularly in the hijab segment. This intense competition requires companies to maintain high product quality and implement effective promotional strategies to create consumer satisfaction. Rabbani, as one of Indonesia’s national Muslim fashion brands, faces challenges related to declining consumer perceptions of product quality and promotional effectiveness, which have an impact on consumer satisfaction, especially in Rancaekek District, Bandung Regency. This study aims to examine and analyze the influence of product quality and promotion on consumer satisfaction among Rabbani hijab users in Rancaekek District, Bandung Regency, both partially and simultaneously. This research employs a quantitative approach using descriptive and verificative methods. The population of this study consists of consumers who use Rabbani hijabs in Rancaekek District, with a sample of 96 respondents selected through purposive sampling. Data were collected through questionnaires developed based on indicators of product quality, promotion, and consumer satisfaction. The data analysis techniques used include descriptive analysis to describe the condition of each variable and multiple linear regression analysis to test the influence of product quality and promotion on consumer satisfaction. The analysis was also supported by classical assumption tests, coefficient of determination tests, and hypothesis testing through partial tests (t-test) and simultaneous tests (F-test). The results of the study indicate that product quality and promotion have a positive and significant effect on consumer satisfaction, both partially and simultaneously. Good product quality and attractive, well-targeted promotional strategies are able to enhance consumer satisfaction with Rabbani products. Therefore, it is recommended that Rabbani place greater emphasis on maintaining consistent product quality and optimizing promotional strategies to improve consumer satisfaction and loyalty amid increasingly competitive conditions in the Muslim fashion industry.